Structural Elucidation of a Novel Lipooligosaccharide from the Antarctic Bacterium OMVs Producer Shewanella sp. HM13 - Angela Casillo; Rossella Di Guida; Sara Carillo; Chen Chen; Kouhei Kamasaka; Jun Kawamoto; Tatsuo Kurihara; Maria Michela Corsaro (Marine Drugs, 2019)
Shewanella sp. HM13 is a cold-adapted Gram-negative bacterium isolated from the intestine of a horse mackerel. It produces a large amount of outer membrane vesicles (OMVs), which are particles released in the medium where the bacterium is cultured. This strain biosynthesizes a single major cargo protein in the OMVs, a fact that makes Shewanella sp. HM13 a good candidate for the production of extracellular recombinant proteins. Therefore, the structural characterization of the components of the vesicles, such as lipopolysaccharides, takes on a fundamental role for understanding the mechanism of biogenesis of the OMVs and their applications. The aim of this study was to investigate the structure of the oligosaccharide (OS) isolated from Shewanella sp. HM13 cells as the first step for a comparison with that from the vesicles. The lipooligosaccharide (LOS) was isolated from dry cells, purified, and hydrolyzed by alkaline treatment. The obtained OS was analyzed completely, and the composition of fatty acids was obtained by chemical methods. In particular, the OS was investigated in detail by 1H and 13C NMR spectroscopy and MALDI-TOF mass spectrometry. The oligosaccharide was characterized by the presence of a residue of 8-amino-3,8-dideoxy-manno-oct-2-ulosonic acid (Kdo8N) and of a d,d-heptose, with both residues being identified in other oligosaccharides from Shewanella species.